TEACHER’ PERCEPTIONS ON THE IMPLEMENTATION OF SCIENTIFIC APPROACH STEPS IN TEACHING READING AT STATE SENIOR HIGH SCHOOL 2 OF TUNGKAL JAYA - Ferri Hidayad; Yus Vernandes Uzer; Siti Yulaikah, Siti Yulaikah (CV. Fahr Publishing, 2023)
The purpose of this study was to find out teachers perception on the implementation scientific approach steps in teaching reading at Senior High School 2 of Tungkal Jaya. The method of this study was qualitative descriptive method. The techniques of collecting data was using interview, observation and documentation. To analyze the data, the writer used thematic analysis. From the research that had been done, the result of the study were: (1). Based on the observation, the researcher found the teachers only applied some of the five steps in scientific approach. They only did observing, questioning, associating and communicating. They sometimes did only questioning, associating, and communicating. (2). The researcher concluded that the teachers’ perception of the Scientific Approach is a concept where the teacher only a facilitator and student-centered. The scientific Approach makes students understand the material by implementing observing, questioning, experimenting, associating, and communicating. Keywords : Reading, Implementation, Scientific approach